Morfometric analysis of pig vertebrae to establish biomechanic correlation with human vertebrae in experimental studies - Rodríguez Cañizo, Ricardo Gustavo; Fuerte H, Ariel; Urriolagoitia S, Guillermo; Merchán C, Emmanuel Alejandro; González R, Alejandro (Revista Mexicana de Ingenieria Biomedica, 2018)
Nowadays, the experimental use of animal models in medicine and biomechanics has allowed the development of new drugs, novel surgical procedures, more efficient and resistant prosthetic devices, etc. However, the reported results found in literature prove to be insufficient and inconclusive to establish which animal model is more adequate to be used as reference for specific research purposes. Therefore, this work focuses in the morphologic analysis of porcine vertebrae of the lumbar section (L3-L4) obtained from young male specimens. The aim of this study is to validate these as an alternate model for experimental research on the biomechanics of the human spine. To this end, ten L3 and ten L4 soft tissue clean porcine vertebral specimens were analyzed. The obtained results showed that in comparison, morphologically, the human vertebrae are shorter and wider than the porcine sample. In general, the porcine vertebrae dimensions increase in the direction from the skull to the lumbar section. However, despite the morphological differences, the anatomical similitude of the spine between both species makes the porcine specimen a viable candidate to be used in biomechanical research of the human lumbar vertebrae as long as such morphological differences are taken into account.